The determinants of agricultural output and the role of food aid: the case of Sub-Saharan Africa. (2017) - Panday, Priniti
This paper investigates factors that influence agricultural output in a group of Sub-Saharan African countries, with special emphasis on the role of food aid. A three-sector trade theoretic framework of an agrarian economy, comprising of exportables, importables and non-traded goods, serves as a basis for the study. This sectorial analysis allows us to analyse movement of resources and demand across sectors, resulting from changes in relative prices, due to food aid. The theoretical model provides various hypotheses that are tested empirically. Results indicate that food aid had a significant negative impact on all three categories of agricultural output. The effect of other variables on the output of the three sectors was also analysed. Factors of production along with a durable and stable regime generally impacted output positively. Drought and conflicts had a significant negative impact on importables and non-traded goods.